Application of a VP4/VP2-inferred transmission clusters in estimating the impact of interventions on rhinovirus transmission - Ng, Kim Tien; Ng, Liang Jie; Oong, Xiang Yong; Chook, Jack Bee *; Chan, Kok Gan; Takebe, Yutaka; Adeeba Kamarulzaman; Tee, Kok Keng (BioMed Central, 2022)
Background: Despite the clinical burden attributable to rhinovirus (RV) infections, the RV transmission dynamics and the impact of interventions on viral transmission remain elusive.